2018
DOI: 10.1093/epirev/mxy001
|View full text |Cite
|
Sign up to set email alerts
|

Active Case Finding for Communicable Diseases in Prison Settings: Increasing Testing Coverage and Uptake Among the Prison Population in the European Union/European Economic Area

Abstract: Prison populations are disproportionally affected by communicable diseases when compared with the general community because of a complex mix of socioeconomic determinants and environmental factors. Tailored and adequate health care provision in prisons has the potential to reach vulnerable and underserved groups and address their complex needs. We investigated the available evidence on modalities and effectiveness of active case-finding interventions in prisons by searching PubMed, Embase, and the Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 82 publications
0
29
1
3
Order By: Relevance
“…Realizing this important public health opportunity is contingent on reliably identifying those with infections. In their review of active case finding for infectious diseases in prisons, Tavoschi et al ( 27 ) found evidence that both testing at prison reception and provider-initiated testing in prison were associated with higher uptake of testing. However, the proportion of prisoners undergoing testing varied markedly between studies, and the methodological quality of most included studies was rated as very poor.…”
Section: Infectious Diseases In Prisonmentioning
confidence: 99%
“…Realizing this important public health opportunity is contingent on reliably identifying those with infections. In their review of active case finding for infectious diseases in prisons, Tavoschi et al ( 27 ) found evidence that both testing at prison reception and provider-initiated testing in prison were associated with higher uptake of testing. However, the proportion of prisoners undergoing testing varied markedly between studies, and the methodological quality of most included studies was rated as very poor.…”
Section: Infectious Diseases In Prisonmentioning
confidence: 99%
“…Studies show that available evidence on the implementation of cases nding strategies in penitentiary settings is limited and inconclusive. However, it is recognized that active case-nding, when comparing with passive case-nding, promotes early diagnosis and allows the treatment of affected individuals, even in asymptomatic stages, therefore, preventing disease transmission both within the prison and to the general population [26][27][28]. The studies have also pointed out that the use of less invasive and rapid tests has proven to be successful in prison environments, reaching greater acceptability to the application of tests [26,29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on diagnosis and treatment strategies in penitentiary settings are limited. However, it is recognized that active case-nding, when comparing with passive case-nding, promotes early diagnosis and allows the treatment of affected individuals, even in asymptomatic stages, therefore, preventing disease transmission both within the prison and to the general population [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The studies have also pointed out that the use of less invasive and rapid tests has proven to be successful in prison environments, resulting in increased application of testing [26,29].…”
Section: Discussionmentioning
confidence: 99%